The role of education in the self-compilation of asthma control test score in patients with asthma. - Dragonieri, Silvano; Quaranta, Vitaliano Nicola; Scisci, Enrico; Capozza, Elena; Barratta, Federica; De Candia, Maria Luisa; Carpagnano, Giovanna Elisiana (Acta Biomedica Atenei Parmensis, 2022)
BACKGROUND. Asthma Control Test (ACT) is a quick and easy tool that allows physicians to estimate the control of asthma symptoms. Previous studies showed that ACT can be self or physician-administered with similar results. AIM. The aim of our study was to evaluate the role of instruction in the self-compilation of ACT and its difference with the physician-administered modality. METHODS. We enrolled 114 patients with asthma from those attending our outpatient clinic. We divided our population into 3 groups, according to their level of education: 1) low level (primary, middle school; n= 34, age 54.3±11.1), 2) middle level (secondary school; n=44, age 38.2±13.8) and 3) high level (university degree; n=34, age 44.8±14.7). All participants answered the questionnaire in both self- and physician-administered ways. Then, we calculated the parameter ΔACT, defined as the difference between physician-administered and self-administered ACT score. The comparison of ΔACT among groups was assessed by Mann-Whitney U test. Moreover, Spearman correlation was used to assess linear relationship between physician- and self-administered ACT in the three groups. RESULTS. Patients with low and middle education level had higher median ΔACT compared to individuals with high education level (2.17 and 2.15 vs 0.75, p<0.05 for both analysis). Moreover, the R2 value of the high education group (0.915) was higher than those with middle and low education (0.642 and 0.773, respectively). CONCLUSIONS. Our data suggest that patients without high education levels tend to overestimate their perception of asthma symptoms. Thus, ACT should always be physician-administered in these asthmatic patients.